Incidenceof Tuberculosis in Unidentified Dead Bodies amongst Autopsy Conducted at Government Stanley Medical College and Hospital, Chennai - A.Gokulakrishnan1 , S.Praveen1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
A autopsy based prospective study on incidence of tuberculosis was conducted at government Stanley medical college for two year from June 2016 –June 2018in that 425 cases of unidentified bodies were subjected for postmortem in that 376 cases were taken for the present study these based on exclusion criteria during autopsy in that 201 cases were male and 175 cases were female, in all the cases sterile swabs were taken from intra bronchial region and directly from caseous necrosed sites and lung tissues from pathological sites are subjected for histopathological examination during autopsy and sterile swabs were subjected for acid fast staining and culture by lowenstien Jensen medium medium among the376 cases studied 52 cases had pulmonary tuberculosis and 2 cases had milliary and intestinal tuberculosis respectively.